(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Total thyroidectomy can safely be performed by bilateral superficial cervical plexus blockade which is a regional anesthetic technique to anaesthetize superficial branches of the anterior primary rami of cervical 3-5 spinal nerves. Conscious sedation with this anesthetic technique enhance safe and faster recovery compared to general anesthesia (GA) with endotracheal intubation which is traditionally employed technique for thyroidectomy. This randomized active control trial was conducted in the department of Anaesthesia, Analgesia and Intensive care medicine, Bangabandhu Sheikh Mujib Medical University from January to December 2018 to compare perioperative outcome between bilateral superficial cervical plexus blockade and GA technique during total thyroidectomy. Total 60 patients of American Society of Anesthesiol- ogists Classification grade I and II who were selected for thyroidectomy were randomly divided into Group-A(n=30) and Group-B (n=30). Group A received with 0.5% bupivacaine and 1% lignocaine; and group B received general anesthesia during total thyroidectomy. Heart rate, systolic blood pressure, diastolic blood pressure mean arterial blood pressure , oxygen satura- tion (SPO2) were recorded and compared between the groups. Operative site bleeding, surgeon’s satisfaction & post operative pain were measured with Boezaart Scoring system, Likert scale & visual analogue scale repectively; and compared between two groups. During induction, systolic and diastolic blood pressure were high in group B and reduced in group A which were statistically significant. Systolic and diastolic blood pressure was significantly reduced in Group-A in comparison to Group-B after 5 minutes, 30 minutes, 45 minutes and at the end of operation. Bilateral superficial cervical plexus blockade reduced pain more effective- ly than GA group & it was statistically significant. Mean value of bleeding score were also statis- tically significant in Group-A. Regarding surgeons’ satisfaction, there was no statistically signif- icant difference between the groups. Bilateral superficial cervical plexus block with conscious sedation provided better outcome in terms of perioperative hemodynamics, pain and surgical site bleeding compared to general anaesthesia. BSMMU J 2021; 14(4): 104-108